Synthesis and in vitro evaluation of novel pH-triggered biocompatible folate-chondroitin sulfate-dexamethasone copolymers for delivery of tofacitinib in rheumatoid arthritis - Zahra Ansarypour; Jaber Emami; Farshid Hassanzadeh; Mahmoud Aghaei; Mohsen Minaiyan; Neal M. Davies; Mahboubeh Rezazadeh (Research in Pharmaceutical Sciences, 2025)
Background and purpose: Rheumatoid arthritis (RA) is a chronic inflammatory disease associated with systemic complications and progressive disability. Systemic side effects and poor drug delivery to joints limit current treatments. This study aimed to enhance the efficacy of tofacitinib (Tofa) by synthesizing novel pH-triggered biocompatible polymers, both folate-targeted and non-folate-targeted. Experimental approach: First-generation polymers were synthesized and characterized using FT-IR and 1HNMR spectroscopy. The critical micelle concentration of the copolymers was evaluated, and Tofa-loaded micelles were prepared using the dialysis method. The physical properties of the micelles were assessed using FE-SEM and dynamic light scattering. Cytotoxicity of Tofa/chondroitin sulfate-maleic-dexamethasone (Tofa/CHS-Mal-DEX) and Tofa/folic acid-polyethylene glycol-chondroitin sulfate-maleic-dexamethasone (Tofa/FA-PEG-CHS-Mal-DEX) micelles was evaluated on the fibroblastic L929 and RAW264.7. The cellular uptake and anti-inflammatory effects were investigated in the activated Raw 264.7 cell line. Findings/Results: Tofa/CHS-Mal-DEX and Tofa/FA-PEG-CHS-Mal-DEX micelles exhibited particle sizes of 188 nm and 173.06 nm, respectively, with entrapment efficiencies of 51% and 72.76%. The release profiles exhibited that about 40% of Tofa was released from micelles over 62 h in physiological pH, whereas in acidic conditions, this significantly decreased to 2 h. Micelles demonstrated improved uptake efficiency, resulting in a significant reduction in IL-6 levels compared to free Tofa. None of the micelle formulations indicated cytotoxic effects on fibroblastic L929 and Raw 264.7 macrophage cell lines. Conclusion and implications: The developed folate and non-folate-targeted micelles were not toxic and biocompatible for enhancing the therapeutic potential of Tofa in RA and improving drug delivery.